PHYSICO-CHEMICAL STUDIES OF APITOXIN AND PRODUCTS ON ITS BASIS - L. I. Butenko; S. A. Kuleshova; J. V. Podgornaya; L. P. Myikots; A. B. Dmitriev (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2018)
Introduction. Nowadays, it is vitally important to develop a method for quantifying melittin not only in apitoxin samples, but also in the products of its processing.The aim of our study is to investigate physical and chemical characteristics of melittin, the main component of apitoxin, as well as the development of methods for the quantitative determination of melittin in the samples of apitoxin and in the pharmaceutical products derived from apitoxin: "Sophia with apitoxin" cream and "Apizartron" ointment.Materials and methods. The objects of the research were apitoxin and melittin, as well as the samples of "Sophia with apitoxin" cream and "Apizartron" ointment satisfying the requirements of regulatory documentation, produced in lots by domestic and foreign manufacturers. The UV spectra of melittin and apitoxin were registered on SF 103 spectrophotometer in quartz cuvettes with 1 cm thickness. The IR spectra were investigated on the IR-instrument of Fourier - FSM-1201 spectrophotometer, LLC "Infraspek". The determination of melittin purity was carried out by chromatography.Results and discussion. The basic physical and chemical characteristics were established for melittin as a reference sample and the main component of apitoxin. The melting temperature was: (Tmelt.)=190ºС. In the UV-spectrum there could be watched the absorption maxima corresponding to 2 peaks: λ max = 225±2 nm and 285±2 nm were observed. As an analytical wavelength, it is necessary to choose the peak λ =285 nm, since the peak with λ =225 nm is associated with the absorption of light by the internal (shielded) benzene ring of the tryptophan molecule. The nature of the curve and the position of the maxima of the spectra of melittin and the apitoxin solution coincide, which makes it possible to use melittin as a standard for spectrometric quantitative determination of the active substances in apitoxin and preparations based on apitoxin.Conclusion. The worked out spectrophotometric methods for the quantitative determination of melittin in apitoxin has been validated by the indices of specificity, accuracy, detection limit, quantitative determination limit, linearity.